Nuclear export mechanisms of circular RNAs: size does matter - Azmi, Asfar S. (Non-coding RNA Investigation; Vol 2 (September 2018): Non-coding RNA Investigation, 2018)
Non-coding RNAs (ncRNAs) are broadly classified as house-keeping and regulatory ncRNAs. The house keeping ncRNAs include the ribosomal RNA, transfer RNA, small nuclear RNA and snoRNA. While the regulatory ncRNA classification is based on length and include shorter microRNAs, snRNAs, piRNAs or the long ncRNAs (lncRNAs) that are greater than 200 nucleotides (nt) (1).